Interplay between global and pathway-specific synaptic plasticity in CA1 pyramidal cells - Berberich, Sven; Pohle, Jörg; Koehr, Georg (Scientific reports, 2017)
Mechanisms underlying information storage have been depicted for global cell-wide and pathway-specific synaptic plasticity. Yet, little is known how these forms of plasticity interact to enhance synaptic competition and network stability. We examined synaptic interactions between apical and basal dendrites of CA1 pyramidal neurons in mouse hippocampal slices. Bursts (50 Hz) of three action potentials (AP-bursts) paired with preceding presynaptic stimulation in stratum radiatum specifically led to LTP of the paired pathway in adult mice (P75). At adolescence (P28), an increase in burst frequency (>50 Hz) was required to gain timing-dependent LTP. Surprisingly, paired radiatum and unpaired oriens pathway potentiated, unless the pre-post delay was shortened from 10 to 5 ms, which selectively potentiated paired radiatum pathway, since unpaired oriens pathway decreased back to baseline. Conversely, the exact same 5 ms pairing in stratum oriens potentiated both pathways, as did AP-bursts alone, which potentiated synaptic efficacy as well as current-evoked postsynaptic spiking. L-type voltage-gated Ca2+ channels were involved in mediating synaptic potentiation in oriens, whereas NMDA and adenosine receptors counteracted unpaired stratum oriens potentiation following pairing in stratum radiatum. This asymmetric plasticity uncovers important insights into alterations of synaptic efficacy and intrinsic neuronal excitability for pathways that convey hippocampal and extra-hippocampal information.
Gesehen am 15.05.2018